2cos pi/13 cos 9pi/13+ cos 3pi/13 +cos 5pi/13
=cos 10 pi/13 +cos 8 pi/13 +cos 3pi/13 +cos 5pi/13
=cos 10 pi/13 +cos 3pi/13 +cos 8pi/13 +cos 5pi/13
=2 cos pi/2 .cos 7 pi/26 +2 cos pi/2 .cos 3 pi /26
=2 (0)cos 7 pi /26 + 2(0) cos 3pi/26
=0 =R.H.S.
Answer: see proof below
Explanation:
Use the following identities:
2cos x · cos y = cos(x + y) + cos(x - y)
cos x + cos y = 2 cos (x + y)/2 · cos(x - y)/2
Use the Unit Circle to evaluate: cos(π/2) = 0
Proof LHS → RHS
Product of Zero 0
LHS = RHS: 0 = 0
5.8m questions
7.5m answers